Spin dependent conductance of a quantum dot side attached to topological superconductors as a probe of Majorana fermion states - Krychowski, Damian; Lipinski, S.; Cuniberti, Gianaurelio (Giovanni) (Acta Physica Polonica A, 2018)
Spin-polarized transport through a quantum dot side attached to a topological superconductor and coupled to a pair of normal leads is discussed in Coulomb and Kondo regimes. For discussion of Coulomb range equation of motion method with extended Hubbard I approximation is used and Kondo regime is analyzed by Kotliar-Ruckenstein slave boson approach. Apart from the occurrence of zero bias anomaly the presence of Majorana states reflects also in splitting of Coulomb lines. In the region of Coulomb borders the spin dependent negative differential conductance is observed. Due to the low energy scale of Kondo effect this probe allows for detection of Majorana states even for extremely weak coupling with topological wire. In this range no signatures of Majorana states appear in Coulomb blockade dominated transport.
CRIS-Team Scopus Importer:2022-04-14